2017
DOI: 10.7498/aps.66.010501
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the directed transport efficiency of feedback-control ratchet

Abstract: Brownian motion in the environment of the thermal fluctuations is a long-study issue in nonequilibrium statistical physics. In recent years, the directed transport properties of Brownian ratchets attract the widespread attention of scholars. When a ratchet system possesses the spatio-temporal symmetry-breaking feature, the directed transport can be produced. Although the breakthrough progress in the directed transport of the Brownian ratchet has been made, the energy conversion efficiency of feedback ratchet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[5,11] It can be concluded that the correlated noises play a great role in the nonequilibrium motion process. In addition, there were also some studies on rocking ratchets, [12,13] the inertia ratchets, [14] feedback-control ratchet, [15] uncoupled neuron system, [16] the static bias, [17][18][19] mass separation, [20] entropy barrier, [21] the motion of fiber suspension, [22] nonmarkovian effect, [23] etc.…”
Section: Introductionmentioning
confidence: 99%
“…[5,11] It can be concluded that the correlated noises play a great role in the nonequilibrium motion process. In addition, there were also some studies on rocking ratchets, [12,13] the inertia ratchets, [14] feedback-control ratchet, [15] uncoupled neuron system, [16] the static bias, [17][18][19] mass separation, [20] entropy barrier, [21] the motion of fiber suspension, [22] nonmarkovian effect, [23] etc.…”
Section: Introductionmentioning
confidence: 99%